Identification of miRNAs Contributing to the Broad-Spectrum and Durable Blast Resistance in the Yunnan Local Rice Germplasm - Li, Jinlu; Zhang, Hui; Yang, Rui; Zeng, Qianchun; Han, Guangyu; Du, Yunlong; Yang, Jing; Yang, Genhua; Luo, Qiong (Frontiers in Plant Science, 2021)
MicroRNAs (miRNAs) are 20-24 nucleotide noncoding RNAs, play important roles in plant-environment interactions. In recent years, many miRNAs have been found to regulate rice immunity against rice blast fungus. However, there are few reports about miRNAs that directly target R genes to regulate rice immunity. In this study, by deep sequencing small RNA libraries constructed from four-leaf stage seedling of resistant variety Ziyu44 and susceptible variety Jiangnanxiangnuo (JNXN) upon Magnaporthe. oryzae infection, we found much more miRNAs were significantly differentially expressed in Ziyu44 than in JNXN. Among of these miRNAs, we focused on miR9664, a new identified rice miRNA in our sequencing, which was up-regulated lightly in Ziyu44 and drastically in JNXN at 24-48 hours post-inoculation (hpi). The transgenic plants overexpressing miR9664 (miR9664-oe) displayed reduced defense responses to M. oryzae, while the transgenic plants knocking down miR9664 (miR9664-m) displayed enhanced defense responses to M. oryzae. Most of miR9664 predicted target genes detected were reduced in miR9664-oe lines while increased in miR9664-m lines, the cleavage site of LOC_Os08g07774 was confirmed by RLM-RACE. Meanwhile, after inoculated with M. oryzae, these genes expressed differently between Ziyu44 and JNXN. These results suggest that miR9664-mediated resistance (R) genes turnover contribute to Ziyu44 broad-spectrum resistance to rice blast fungus. Taken together, our research identified a new rice miRNA that directly targets R genes to regulate rice immunity against rice blast fungus, this adds some meaningful information to the study of rice-M. oryzae interaction.